2022
DOI: 10.3390/biom12020304
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Regulatory Roles of Long Non-Coding RNAs in Periodontal Ligament Cells: A Systematic Review

Abstract: Periodontal ligament (PDL) cells play a pivotal role in periodontal and bone homeostasis and have promising potential for regenerative medicine and tissue engineering. There is compelling evidence that long non-coding RNAs (lncRNAs) are differentially expressed in PDL cells compared to other cell types and that these lncRNAs are involved in a variety of biological processes. This study systematically reviews the current evidence regarding the expression and regulatory functions of lncRNAs in PDL cells during v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…The molecular mechanism of rescuing the PDL cells of inflamed periodontal tissue and improving their regenerative potential has long been discussed. 15,17,18,21,38 Recent evidence has suggested that AKT signaling is related to the osteogenic differentiation of PDL cells, 39,40 and the activation of AKT signaling restores Toll-like receptormediated inhibition of osteogenic differentiation in PDL cells. 40 Our results show that after osteogenic induction, AKT signaling was less activated in I-PDL and S-PDL cells than in H-PDL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of rescuing the PDL cells of inflamed periodontal tissue and improving their regenerative potential has long been discussed. 15,17,18,21,38 Recent evidence has suggested that AKT signaling is related to the osteogenic differentiation of PDL cells, 39,40 and the activation of AKT signaling restores Toll-like receptormediated inhibition of osteogenic differentiation in PDL cells. 40 Our results show that after osteogenic induction, AKT signaling was less activated in I-PDL and S-PDL cells than in H-PDL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of included papers was assessed using a quality scoring system, 47 which included eight questions and has been widely used in similar publications with "yes" and "no" answers assigned 1 and 0 points, respectively. [48][49][50][51] The maximum achievable score is 8 points. The quality scores for included studies were independently determined.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A score of 7-8 was interpreted as excellent, 5-6 as good, 3-4 as poor, and 0-2 as bad. [48][49][50][51]…”
Section: Quality Assessmentmentioning
confidence: 99%
“… 14 Recent studies have demonstrated that lncRNAs mediate mechanical stress‐induced osteogenic mineralization of periodontal ligament stem cells (PDLSCs) to control periodontal homeostasis. 15 , 16 Also playing a role in periodontal homeostasis and acting as the primary root cell type to sense orthodontic forces, 17 cementocytes could likewise transduce mechanical signals 5 , 17 into biological responses that modulate cementum mineralization in a lncRNAs‐based regulatory manner. However, the potential mechanisms of such cellular events are yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a post‐transcriptional regulation manner, lncRNA SNHG1 upregulated DNA methyltransferase 1 (DNMT1) expression, resulting in osteoprotegerin (OPG) hypermethylation and decreased OPG expression, in turn contributing to osteoporosis 14 . Recent studies have demonstrated that lncRNAs mediate mechanical stress‐induced osteogenic mineralization of periodontal ligament stem cells (PDLSCs) to control periodontal homeostasis 15,16 . Also playing a role in periodontal homeostasis and acting as the primary root cell type to sense orthodontic forces, 17 cementocytes could likewise transduce mechanical signals 5,17 into biological responses that modulate cementum mineralization in a lncRNAs‐based regulatory manner.…”
Section: Introductionmentioning
confidence: 99%